2013
DOI: 10.3389/fphar.2013.00147
|View full text |Cite
|
Sign up to set email alerts
|

Current clinical evidence on pioglitazone pharmacogenomics

Abstract: Pioglitazone is the most widely used thiazolidinedione and acts as an insulin-sensitizer through activation of the Peroxisome Proliferator-Activated Receptor-γ (PPARγ). Pioglitazone is approved for use in the management of type 2 diabetes mellitus (T2DM), but its use in other therapeutic areas is increasing due to pleiotropic effects. In this hypothesis article, the current clinical evidence on pioglitazone pharmacogenomics is summarized and related to variability in pioglitazone response. How genetic variatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 72 publications
1
17
0
1
Order By: Relevance
“…Pathogenesis and treatment of inflammatory gut barrier failure is an important problem in critical care. The PPARg agonist pioglitazone is the most widely used thiazolidinedione (TZD) antidiabetic drug and currently the only TZD available without regulatory restrictions [29]. It is an oral drug usually provided in the form of a tablet, and no intravenous forms are available in clinical medicine for now.…”
Section: Discussionmentioning
confidence: 99%
“…Pathogenesis and treatment of inflammatory gut barrier failure is an important problem in critical care. The PPARg agonist pioglitazone is the most widely used thiazolidinedione (TZD) antidiabetic drug and currently the only TZD available without regulatory restrictions [29]. It is an oral drug usually provided in the form of a tablet, and no intravenous forms are available in clinical medicine for now.…”
Section: Discussionmentioning
confidence: 99%
“…and triglycerides in carriers of the 12Ala allele 164,[172][173][174] despite two studies observed no association, 175,176 and one reported that insulin levels and insulin resistance were lower in carriers of the Pro12Pro genotype after PIO treatment. 172 In response to ROSI, Korean T2DM patients carrying the 12Ala variant have been shown to have significantly greater decrease in fasting glucose levels and HbA1c.…”
Section: Polymorphisms Affecting Tzds Responsementioning
confidence: 94%
“…PPARG is a nuclear receptor serving as lipid sensor and the cognate receptor for TZDs; its most common variant, rs1801282 (Pro12Ala), reproducibly associated with decreased risk of T2DM, has been widely addressed in pharmacogenetics studies on TZDs efficacy. Several reports have been meta‐analysed revealing a better response to PIO treatment in terms of improvements in fasting glucose, HbA1c and triglycerides in carriers of the 12Ala allele despite two studies observed no association, and one reported that insulin levels and insulin resistance were lower in carriers of the Pro12Pro genotype after PIO treatment . In response to ROSI, Korean T2DM patients carrying the 12Ala variant have been shown to have significantly greater decrease in fasting glucose levels and HbA1c .…”
Section: Summary Of the Literaturementioning
confidence: 99%
“…After single oral administration or continuous oral administration, the blood active metabolic concentrations in female mice were higher than that in male mice (1.5-3 times) [34] . CYP2C8 is a critical enzyme in the metabolism of pioglitazone, and carrying the CYP2C8*3 allele will accelerate the metabolism of pioglitazone [35] . A population study showed that NASH patients with the CYP2C8*3 allele had less improvement in liver fibrosis after pioglitazone intervention (p = 0.006) [36] .…”
Section: Trial (Adopt) and Rosiglitazone Evaluated For Cardiovascularmentioning
confidence: 99%